Non-Traditional Financing for Costa Rican MSMEs - Palma Rodríguez, Carlos (2008)
The object of this investigation was to study the current situation of the micro, small and median (MIPYMES) Costa Rican companies, to investigate the requirements for its constitution and the stages of its development, its objectives and its growth, as they have a high importance for the social and economic development of Costa Rica. It also describes the kind of financial and support that is used by the traditional and non traditional banks in order to analyze the necessity to create a different financial system for those types of companies. This financial system shall not meet all require- ments of the “Superintendencia General de Entidades Financieras” (SUGEF of Costa Rica) because small enterprises cannot meet them, but it shall be a new, specialized financial system.